THE EMPOWERMENT OF CIVIL PREPAREDNESS IN MALAYSIA TOTAL DEFENCE (HANRUH) POLICY: CHALLENGES AND SOLUTIONS - Mohd Kamarul Amree Mohd Sarkam; Noor Azmi Mohd Zainol; Zahimi Zainol Abidin; Zaidi A. Rahman, (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Total Defence or known as Pertahanan Menyeluruh (HANRUH) is one of the core principles of Malaysia's National Defence White Paper (DWP) in pursuit of acquiring national resilience and comprehensive defence capacity. However, due to lack of awareness and enforcement, has garnered less attention among Malaysian citizen as the fundamental basis outline in the principle that includes the civil preparedness approach is vital to deter unexpected war threats as well as to maintain sustainable peace and security in every aspect of national concern. Some of the challenges encountered is the fragility of social cohesiveness and lack of patriotism spirit among few Malaysians. The research data was gathered using qualitative methods that included bibliography and analysis of knowledge sources such as books, journal articles, theses, scientific publications, and interviews with selected informants. The study's findings revealed that civil preparedness was properly designed under the HANRUH policy. As a result, the two challenges mentioned before have a negative impact on efforts to empower citizen participation in national defence. Thus, some of the enforcement made by The Malaysian Government through several policies can provide vital solutions especially on unity and culture among Malaysian citizen.